Techno-Economic and Feasibility Analysis of a Hybrid PV-Wind-Biomass-Diesel Energy System for Sustainable Development at Offshore Areas in Bangladesh - Shezan, S.K.A.; Ping, H.W. (Current Alternative Energy, 2017)
Background: The vast percentage of people of the world; particularly in the developing countries; are living mostly in the decentralized, rural and remote areas which are geographically secluded from the national grid connection. Power distribution and continuous fuel transportation needed to produce the electrical energy for these areas pose a great challenge. Using renewable energy resources in off grid hybrid energy might be a promising solution. Methods: Moreover, high cost of renewable energy systems has led to its slow implementation in many countries. Hence, it is vital to select an appropriate system size in order to reduce the cost as well as to make the use of available resources more efficient. An off-grid hybrid energy system has been designed as well as simulated to support a small community considering an average load demand of 80 kWh/d with a peak load of 8.1 kW. The simulation and optimization of operations of the system have been done by HOMER software using the real time field data of solar radiation, wind speed and biomass of that particular area. The simulation ensures that the system is economically and environmentally feasible with respect to net present cost (NPC) and CO2 emission limitations. Results: The result shows that NPC and CO2 emission can be reduced about 29.65%; equivalent to 16 tons per year as compared to conventional power plants. The NPC of the optimized system has been found to be about USD 160,626.00, having the per unit Cost of Energy (COE) of USD 0.431/kWh. Conclusion: The analyzed hybrid energy system might be applicable for other regions of the world where there are similar climatic conditions.
Keywords: optimization